2019
DOI: 10.1103/physrevb.100.235124
|View full text |Cite
|
Sign up to set email alerts
|

Self-duality of the integer quantum Hall to insulator transition: Composite fermion description

Abstract: The integer quantum Hall to insulator transition (IQHIT) is a paradigmatic quantum critical point. Key aspects of this transition, however, remain mysterious, due to the simultaneous effects of quenched disorder and strong interactions. We study this transition using a composite fermion (CF) representation, which incorporates some of the effects of interactions. As we describe, the transition also marks a IQHIT of CFs: this suggests that the transition may exhibit 'self-duality'. We show the explicit equivalen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…xx requires the renormalized m 2 = 0. The resulting NSLM reduces to that found in [54] in which a θ = π term appears. We interpret this as an emergent particle-hole symmetry and the irrelevance of m 2 near the diffusive quantum critical point.…”
Section: B Detailed Summarymentioning
confidence: 54%
See 3 more Smart Citations
“…xx requires the renormalized m 2 = 0. The resulting NSLM reduces to that found in [54] in which a θ = π term appears. We interpret this as an emergent particle-hole symmetry and the irrelevance of m 2 near the diffusive quantum critical point.…”
Section: B Detailed Summarymentioning
confidence: 54%
“…In [54] the θ = π term was extracted by a careful study of the chiral anomaly of a 2D theory closely related to the one in (3.49). In this earlier study, only particle-hole symmetric disorder was considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been recent progress towards an analytical description of this quantum criticality [19,20]. Specifically in [19] it was shown that the nonlinear sigma model (NLSM) for the diffusion of Dirac composite fermion [15] charge density fluctuations Q ∈ U(2n)/U(n)×U(n),…”
Section: Hlr Theory Generating Functionalmentioning
confidence: 99%